Time as a Dimension of Byzantine Identity - Koder, Johannes (Studia Ceranea, 2019)
The notion of identity (tautotes) was discussed, often in contrast to its opposite “otherness” (heterotes), not only during Classical Antiquity but also by Christian and Byzantine authors since Late Antiquity. Fundamental manifestations of every dimension of Byzantine identity – and in particular of collective identity – are language (including culture), religious (and political) commitment, space and time; these phenomena are deeply rooted in human consciousness. This paper deals with the relation between identity and time (temporality). This relation is analysed on the basis of key terms like aion, kairos and chronos and the relations among them; the individualization of temporality becomes manifest in combinations of the mentioned terms with adjectives like emos or hemeteros. Not surprisingly, Byzantine authors – referring to passages in the Old and the New Testament – dealt mainly with eschatological (cosmic) time in relation to individual and collective identity, whereas the interest in the historical dimension of time was limited to authors of a small educated class.